A review of pharmaceutical and personal care products and atopic dermatitis based on epidemiological and basic research findings - Xie, Shushu; Jiang, Yan; Hu, Zhiqin; Ding, Zhishan; Yu, Jie; Ye, Xiaoqing (Frontiers in Public Health, 2025)
Pharmaceutical and personal care products (PPCPs) are emerging pollutants that have been found to be related to allergic diseases. Currently, a large amount of research focused on the association between PPCPs and atopic dermatitis (AD), but there has been no evaluation of existing evidence on this topic. Here, we reviewed epidemiological and toxicological studies from 2014 to 2024, with a focus on common PPCPs such as antibiotics, phthalates, p-hydroxybenzoic acid, etc. We found that most PPCPs are positively correlated with the onset of AD, with particular attention paid to exposure during pregnancy and infancy. This reminds AD patients to be cautious when taking medication and choosing nursing products. Animal studies have shown that the pathogenesis of PPCPs may be mediated by dysbiosis, immune imbalance and oxidative stress. Despite inconsistent results in existing research, PPCPs are confirmed to be unfavorable drivers of AD occurrence and progression. Clarifying their potential link with AD is critical for informing subsequent policy and regulatory decisions.